Effects of HIV infection and antiretroviral therapy on development of osteopenia [HIV i̇nfeksiyonu ve antiretroviral tedavinin osteopeni gelişimine etkileri] - TİGEN, ELİF; KORTEN, VOLKAN (My University, 2012)
Osteopenia, osteoporosis and osteonecrosis are frequently observed in patients with human immunodeficiency virus (HIV) infection. Low bone mineral density (BMD) is seen in 2-6% of patients with HIV infection within the first 2 years of antiretro-viral therapy. It is generally believed that HIV infection itself and the antiretroviral therapy both contribute to low BMD, together with the traditional risk factors of osteoporosis. Recent studies have demonstrated an increased risk of fracture in HIV-infected patients. Today, it is suggested that all HIV-positive women and men aged over 50 years should be screened for fragility fractures. In this study, the diagnosis and treatment of osteopenia in HIV-infected individuals are discussed.
Keywords: Highly active antiretroviral therapy; HIV; Metabolic bone disease